NEGOSIASI WAKTU RUMAH TANGGA PETANI (Studi Kasus Di Desa Sukawening, Kabupaten Bogor, Jawa Barat) - Pratiwi, Dita; Andarwangi, Tunjung (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Indonesia as an agricultural country still focuses on its development in the agricultural sector, especially in rural areas. Labor in the agricultural sector, especially in rural areas, involves all human resources in the family, including women. This is such an effort to increase the family income, not only men will contribute to family income, but also women contribute to increasing the family income. The purpose of this study is to know the forms of negotiations carried out by farmers in carrying out their work as farmers and also their role in social life and to analyze the division of labor between men and women farmers. This research was conducted in Sukawening Village, Dramaga District, Bogor, West Java. This research used purposive sampling techique.  The consideration for conducting research in Sukawening Village because Sukawening Village is a village with various agricultural potentials from food to horticulture. Based on the results, forms of negotiation carried out by farmers and their families in Sukawening village are random negotiations, negotiations based on ability, systematic negotiations and negotiations based on external factors. There is a division of labor between farmers and their families in Sukawening Village. The division of labor is based on the capabilities possessed by farmers. Because between men and women have their respective expertise in carrying out farming activities.